A case study on the implementation of the Qardhul Hasan concept as a financing product in an Islamic bank in Malaysia - Zainal Abidin, Ahmad; Mohd Ariffin, Noraini; Mohd Alwi, Norhayati (2011)
Qardhul Hasan is a zero-return financing that Al-Quran urges Muslims to make available to those who need them. In addition, Qardhul Hasan is an example of a unique interest free instrument that is offered by Islamic Financial Institutions (“IFIs”). The objective of this paper is to study the implementation of the Qardhul Hasan concept, as a financing product in an Islamic bank in Malaysia. This study adopted a single case study research. This is the best approach, and appropriate to answer the research questions and to achieve the research objective. Furthermore, an exploratory case study has been adopted. As a result, this study found that CALF (Malaysia) Berhad only offers Qardhul Hasan financing to its employees. In addition, the facility is limited for certain purposes, which are for marriage, birth of a child, study and inopportune. As there are only three IFIs in Malaysia that offer Qardhul Hasan, it is hoped that this study can provide the remaining IFIs or other IFIs in the world with a guideline or basis on how to implement Qardhul Hasan financing. It is also believed that this study can be used by regulatory bodies, including Bank Negara Malaysia or the Malaysian Accounting Standard Board, or as a basis for setting up specific accounting and reporting guidelines on Qardhul Hasan.